Elimination of 72-Hour Quantitative Fecal Fat Testing by Restriction, Laboratory Consultation, and Evaluation of Specimen Weight and Fat Globules. (1st November 2018) - Korostensky, Michael; Martin, Steven R; Swain, Mark; Raman, Maitreyi; Naugler, Christopher T; Sadrzadeh, S M Hossein; de Koning, Lawrence
Abstract: Background: The 72-h quantitative fecal fat test has been mostly obsolete for many years. Our objective was to reduce and eliminate the use of this test, while providing suitable alternatives. Methods: We assessed (2010–2016) utilization of the fecal fat test in Calgary, Central Alberta, and Southern Alberta, Canada. Alternatives were identified through literature review and consultation with gastroenterologist stakeholders. Logistic regression and ROC curves were used to characterize discrimination power of 72-h specimen weight on abnormal fat excretion. This was also examined in 91 subspecimens that were additionally tested for the presence of fat globules. Results: As 69% of fecal fat tests (total, 106/year) were on adults (age ≥ 18), stakeholders agreed that adult specimens should not be tested until ordering physicians consulted with a clinical biochemist. This change reduced fecal fat testing by 81% to 20/year in 2015. The 72-h specimen weight was a significant predictor of abnormal fat excretion [ P < 0.001; area under curve (AUC) = 0.75–0.79, n = 115–417] in historic fecal fat data. A similar result was observed among subspecimens (AUC = 0.70), which improved when additionally considering the presence of fat globules (AUC = 0.74). Stakeholders consented to replacing fecal fat with a comparison of specimen weight to cutpoints with 80% specificity for abnormal fat excretion, and the test for fat globules. Conclusion: Through stakeholder engagement, we implemented changes that eliminated 72-h quantitative fecal fat testing in a large geographic region in Alberta, Canada. Future fecal fat orders would be reflexed to an assessment of 72-h specimen weight and a qualitative test for fat globules in stool.